DoA estimation with reflectarray according to single pixel camera principle - Skoblikov, Sergii; Ibrahim, Mohamed; Romer, Florian; Thoma, Reiner S.; Del Galdo, Giovanni (2015 3rd International Workshop on Compressed Sensing Theory and its Applications to Radar, Sonar, and Remote Sensing, CoSeRa 2015, 2015)
This paper suggests using a tunable reflectarray as a hardware source of Sensing Functions (SFs) for Direction of Arrival (DoA) estimation based on Compressed Sensing (CS). Reflectarray is much more scalable than a conventional antenna array. This higher scalability can be exploited to build a measurement hardware with large aperture and high number of degrees of freedom. We introduce the simplified reflectarray propagation model, based on which we propose a number of possible measurement architectures, for each of them we show how the Sensing Matrix (SM) will be defined. Finally, a typical non-sparse beampattern is obtained using numeric simulation.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Compressed Sensing; Direction-of-arrival estimation; Reflectarray